Killing of black and white rhinoceroses by African elephants in Hluhluwe-Umfolozi Park, South Africa - Rob Slotow; Dave Balfour; Owen Howison (Pachyderm)
Between 1991 and 2001 elephants killed 58 white and 5 black rhinos in Hluhluwe-Umfolozi. The culprits were primarily young male elephant entering musth at a younger than normal age due to the absence of older bulls. Elephant bulls (17-25 years) translocated as young animals from Kruger NP culls had no older male hierarchy, and were entering into musth as early as 18 as opposed to an average age of 28. (Poole 1987). Carcasses were often found in the vicinity of rivers, 76% being within 1 km of a river. Rhinos killed were predominately adult (86%), and slightly more males than females. This situation was similar to that in Pilanesberg NP (50 white rhinos killed 1992-1997) which was suppressed when 6 older bulls were introduced. In May 2000 10 older bulls from Kruger NP were introduced to Hluhluwe-Umfolozi. The number of rhino deaths decreased immediately, between September 2000 and October 2001 only 2 were killed (both in June 2001). Results suggest when rhino are present in an area older male elephants should be brought into a population of young introduced animals, but numbers should be on the conservative side monitored to assess vegetation/habitat utilization as well as interspecific aggression.